The Surabaya District Court judge's Ruling in Gregorius Ronald Tannur's Trial Resulted in His Acquittal of the Murder Charge - Pasaribu, Roy Ronaldo M.; Esther, July; Sidauruk, Jinner (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines Gregorius Ronald Tannur's acquittal in a murder case (verdict number 454/Pid.B/2024/PN Sby) and whether it complies with Indonesian legal certainty and justice criteria. Examining the judge's use of legal reasoning in the ruling critically is the aim of this study. Using a normative legal research approach, this study looks at secondary sources in addition to fundamental legal texts like court decisions and the Criminal Code. The findings demonstrate that the judge's decision ignored crucial evidence, such as the visum et repertum detailing the victim's injuries and CCTV footage implicating the defendant. The judge's assertion that the defendant was innocent and had made an effort to help the victim did not align with the evidence that was given throughout the trial. The integrity of the legal system and the possible impact of outside influences on court rulings are seriously called into question by this disparity.Reforming court procedures and enforcing stronger sanctions against judge corruption are crucial for regaining public trust and guaranteeing just and equitable outcomes within the legal system.